Adverse Drug Reactions of Antihypertensives and CYP3A5*3 Polymorphism Among Chronic Kidney Disease Patients - Lee, Fei Yee; Islahudin, Farida; Abdul Gafor, Abdul Halim; Wong, Hin-Seng; Bavanandan, Sunita; Mohd Saffian, Shamin; Md Redzuan, Adyani; Makmor-Bakry, Mohd (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) patients may be more susceptible to adverse drug reactions (ADRs), given their complex medication regimen and altered physiological state driven by decline in kidney function. This study aims to describe the relationship between CYP3A5*3 polymorphism with ADR of antihypertensive drugs in CKD patients. This retrospective, multi-centre, observational cohort study was performed among adult CKD patients with a follow-up period of up to 3 years. ADRs were detected through medical records. CYP3A5*3 genotyping was performed using direct sequencing method. From the 200 patients recruited in this study, 33 (16.5%) were found to have ADRs related with antihypertensive drugs, with 40 ADRs reported. The most frequent ADR recorded was hyperkalaemia (n=8, 20.0%), followed by bradycardia, hypotension and dizziness with 6 cases (15.0%) each. The most common suspected agents were angiotensin II receptor blockers (n=11, 27.5%), followed by angiotensin-converting enzyme inhibitors (n=9, 22.5%). CYP3A5*3 polymorphism was not found to be associated with antihypertensive-related ADR across the genetic models tested, despite adjustment for other possible factors through multiple logistic regression (p>0.05). After adjusting for possible confounding factors, the factors associated with antihypertensive-related ADR were anaemia (adjusted Odds Ratio [aOR] 5.438, 95% confidence interval [CI]: 2.002, 14.288) and poor medication adherence (aOR 3.512, 95% CI: 1.470, 8.388). In conclusion, CYP3A5*3 polymorphism was not found to be associated with ADRs related with antihypertensives in CKD patients, which requires further verification by larger studies.